Gingival Bleeding Index Status Among Orthodontic Patients Treated with Fixed Orthodontic Appliances in a Tertiary Level Hospital (KYAMC Journal, 2018)
Background: Oral hygiene maintenance becomes difficult during fixed orthodontic treatment.Objective: The aim of this study was to assess Gingival Bleeding Index among patients treated with fixed orthodontic appliances in a tertiary level hospital.Metanitil and Methody: This study was conducted on 100 patients treated with fixed orthodontic appliances for more than six months in the OPD of Orthodontics Department at Bangabandhu Sheikh Mujib Medical University, Dhaka from July 2013 to July 2014. All the information related to oral hygiene maintenance like brushing, dental floss use, use of mout hwash during treatment in the OPD were recorded. The Gingival Bleeding Index (GBI) was calculated and recorded. Apart from this, frequency of brushing, type of tooth brush, technique of brushing and inter dental brush were also considered.Result: Over all mean value of GBI was 23.44±17.00. Mean value of GBI was 26.44 ± 15.23 among patients who brushed their teeth once a day but it was decreased gradually as the patients increased frequency of toot hbrush use per day and became 11.55±4.71 among the patients who brushed their teeth thrice a day. Mean value of GBI was 23.46±17.18 who did not use dental floss and 22.85 (12.64) who used dental floss once a day. Mean value of GBI was 25.30±17.73 who used inter dental brush irregularly but 2.75±0.35 who used it thrice a day. Mean value of GBI was25.17±17.69 who did not use mouth wash whereas it reduced to 8.00±0.00 among them who used mouth wash thrice a day.Conclusion: The Gingival Bleeding Index (GBI) is increased in patients treated with fixed orthodontic appliances.KYAMC Journal Vol. 9, No.-3, October 2018, Page 129-132